Políticas regulatórias no Brasil, Canadá, EUA e Portugal (CEE) : estudo comparativo dos diferentes níveis de exigência para o registro de medicamentos genéricos. - Saad, Marcela (2008)
Access to medicines with quality and low price constitutes the fundamental principle of health policies in government programs of different countries. Since their introduction, generic medicines were designed to ensure improved access by the populace, given their identical quality, safety and effectiveness when compared to their reference products and also given their much lower cost. Further, upon creation of this new pharmaceutical category, national health regulatory agencies around the world, through their product registration regulations, developed systems to define and enforce the criteria governing generic medicines. To meet the aforementioned requirements of quality, safety and effectiveness, each country - whether or not using international regulations as its regulatory basis – to some degree varied its requirements for the registration of generic medicines in order to ensure its regulatory sovereignty and in some cases to protect its local production. The objective of this work is to demonstrate the differences between generic medicine registration requirements, of the health regulatory agencies of the countries compared herein. To achieve this goal, comparisons were made between relevant pieces of legislation of selected countries and regions. This work contains the effective regulations applied in each comparative region as well as comments and explanations of the procedures adopted by each one. The main conclusion demonstrated through this work is that the administrative information in the submission of dossiers for registration of generic products is presented in different formats in each country. However, the technical essence of these requirements is not so different in that only the required levels of detail present greater or lesser degrees of difficulty.